2016
DOI: 10.1021/acsenergylett.6b00245
|View full text |Cite
|
Sign up to set email alerts
|

Rational Sulfur Cathode Design for Lithium–Sulfur Batteries: Sulfur-Embedded Benzoxazine Polymers

Abstract: A variety of advanced electrode structures have been developed lately to address the intrinsic drawbacks of lithium–sulfur batteries, such as polysulfide shuttling and low electrical conductivity of elemental sulfur. Nevertheless, it is still desired to find electrode structures that address those issues through an easy synthesis while securing large sulfur contents (i.e., > 70 wt %). Here, we report an orthogonal, “one-pot” synthetic approach to prepare a sulfur-embedded polybenzoxazine (S-BOP) with a high su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 57 publications
3
84
0
Order By: Relevance
“…f) Rate performance of S‐BOP (0.9 mg sulfur cm −2 ). Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Vulcanization/inverse Vulcanization Polysulfide Polymer Basementioning
confidence: 99%
See 1 more Smart Citation
“…f) Rate performance of S‐BOP (0.9 mg sulfur cm −2 ). Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Vulcanization/inverse Vulcanization Polysulfide Polymer Basementioning
confidence: 99%
“…Je et al synthesized sulfur‐embedded polybenzoxazine (S‐BOP, as shown in Figure c) with 72 wt% sulfur. In S‐BOP, the sulfur chains were covalently bonded to the polymer framework through thiol groups present in the BZ monomer.…”
Section: Vulcanization/inverse Vulcanization Polysulfide Polymer Basementioning
confidence: 99%
“…Some representative electrode designs to avoid these fading mechanisms include encapsulating elemental sulfur (S) in conductive porous media or nanomaterial assemblies [35,36] or synthesizing sulfur-embedded polymers. [37][38][39][40][41][42] Both strategies have improved cyclability mainly by mitigating polysulfide dissolution. However, complete encapsulation remains a technical challenge for the former approach, where inevitable defects could lead to polysulfide dissolution especially Polysulfide dissolution into the electrolyte and poor electric conductivity of elemental sulfur are well-known origins for capacity fading in lithium-sulfur batteries.…”
mentioning
confidence: 99%
“…Sulfur-organics copolymers have been wildly investigated in LiÀ S batteries. [41][42][43][44] These copolymers are usually prepared by heating sulfur and organics under controlled temperature and atmosphere. During the heating process, sulfur could copolymerize with the organics and form the sulfur-organics copolymers.…”
Section: Sulfurà Organics Copolymersmentioning
confidence: 99%